AbÃ» Naá¹£r al-SarrÃ¢j dan Wacana Sufistik Lintas Disiplin Keilmuan - Riyadi, Abdul Kadir (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This paper traces back the origin of tasawuf to the early period of Islam by investigating the ideas propagated by one of its best scholars named Abû Nasr al-Sarrâj. The paper tries to find the link between his thought and that of the earlier sufis on the one hand, and his response to the social and epistemological contexts that shape it on the other. In doing so, it discusses first the debate and the so-called dynamic tension in which the sufis and their opponents were involved. The paper shows that the development of tasawuf cannot be separated from this tension as well as from what the sociologists of knowledge have taught us to call falsification. Tasawuf was dubbed the distorted version of Islam and was falsified in such a way that many sufis ended up in being alleged apostate. However, having succeeded in going through this phase of history made tasawuf an objective and paradigmatic kind of knowledge. The thought of al-Sarrâj?the paper argues?is reminiscent of this form of knowledge. His is a kind of thought that brings forth not only new ideas and concepts, but also strategies of survival and method of thinking quite new for its context; method that may be deemed multidisciplinary in its form and objective.